Impact of policy support on uptake of evidence-based continuous quality improvement activities and the quality of care for Indigenous Australians: a comparative case study. Issue 10 (5th October 2017) - Bailie, Ross; Matthews, Veronica; Larkins, Sarah; Thompson, Sandra; Burgess, Paul; Weeramanthri, Tarun; Bailie, Jodie; Cunningham, Frances; Kwedza, Ru; Clark, Louise
Abstract : Objectives: To examine the impact of state/territory policy support on (1) uptake of evidence-based continuous quality improvement (CQI) activities and (2) quality of care for Indigenous Australians. Design: Mixed-method comparative case study methodology, drawing on quality-of-care audit data, documentary evidence of policies and strategies and the experience and insights of stakeholders involved in relevant CQI programmes. We use multilevel linear regression to analyse jurisdictional differences in quality of care. Setting: Indigenous primary healthcare services across five states/territories of Australia. Participants: 175 Indigenous primary healthcare services. Interventions: A range of national and state/territory policy and infrastructure initiatives to support CQI, including support for applied research. Primary and secondary outcome measures: (i) Trends in the consistent uptake of evidence-based CQI tools available through a research-based CQI initiative (the Audit and Best Practice in Chronic Disease programme) and (ii) quality of care (as reflected in adherence to best practice guidelines). Results: Progressive uptake of evidence-based CQI activities and steady improvements or maintenance of high-quality care occurred where there was long-term policy and infrastructure support for CQI. Where support was provided but not sustained there was a rapid rise and subsequent fall in relevant CQI activities. Conclusions: Health authorities should ensure consistent and sustained policy and infrastructure support for CQI to enable wide-scale and ongoing improvement in quality of care and, subsequently, health outcomes. It is not sufficient for improvement initiatives to rely on local service managers and clinicians, as their efforts are strongly mediated by higher system-level influences.